2016
DOI: 10.1007/s13762-016-0933-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel definitive screening design to decolorization of an azo dye on boron-doped diamond electrodes

Abstract: The electrochemical decolorization of the Reactive Violet 5 azo dye on a boron-doped diamond anode was used as a model process to test a novel definitive screening design (DSD). This method allows a dramatic reduction in the number of experiments needed to investigate those systems characterized by a large number of variables. In this study, the effect of nine quantitative parameters was investigated: initial dye concentration (60-120 mg L -1 ), current density (100-500 A m -2 ), NaCl concentration (5-20 mM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
(26 reference statements)
0
19
0
1
Order By: Relevance
“…However, its complex aromatic structure ( Figure 1) makes it highly resistant to degradation. A literature survey showed that very few studies have been performed on RV5 degradation and none of them investigated the photocatalytic removal of the dye under visible light [27][28][29][30][31][32]. Accordingly, a first aim of this study was to evaluate whether the use of the selected photocatalyst in the presence of visible light could be a suitable method to degrade RV5.…”
Section: Introductionmentioning
confidence: 99%
“…However, its complex aromatic structure ( Figure 1) makes it highly resistant to degradation. A literature survey showed that very few studies have been performed on RV5 degradation and none of them investigated the photocatalytic removal of the dye under visible light [27][28][29][30][31][32]. Accordingly, a first aim of this study was to evaluate whether the use of the selected photocatalyst in the presence of visible light could be a suitable method to degrade RV5.…”
Section: Introductionmentioning
confidence: 99%
“…During the analysis of factors, screening designs must be used to select the parameters that affect the response significantly; however, such parameters are limited and generally need a more detailed study to understand the effects of interaction between such factors [23]. Therefore, a new design called definitive screening design (DSD) with three levels has been proposed by Jones and Nachtsheim [24], which allows screening of factors to obtain information that can clarify details about their effects.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature also reported that in the presence of chlorides, the electrochemical process produces a mixture of chlorine oxidants with high selectivity toward the chromophore group, thus accelerating the color removal rate prior to mineralization [31,32]. …”
Section: Resultsmentioning
confidence: 99%